2009
DOI: 10.1515/jpem.2009.22.5.433
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c and Serum Levels of Advanced Glycation and Oxidation Protein Products in Poorly and Well Controlled Children and Adolescents with Type 1 Diabetes Mellitus

Abstract: Diabetes mellitus is associated with hyperglycemia and with accelerated non-enzymatic glycation, increased oxidative stress and free radical production. The aim of the present study was to evaluate the levels of proteins glycation and oxidation parameters, compare them between poorly and well controlled children with type 1 diabetes mellitus, and determine the impact of glycemic control on these parameters. Blood and serum were obtained from 81 patients with type 1 diabetes mellitus (DM1) (20 patients had long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Within the context of diabetes mellitus, chronic hyperglycemia and acute hyperglycemia produce free radicals and thereby increase levels of oxidative stress. 277 Most [278][279][280][281][282][283][284][285] but not all 286 studies report that oxidative stress levels are higher in youth with T1DM compared with healthy control subjects. Consistent with the hypothesis that uncontrolled hyperglycemia is one of the primary mechanisms responsible for oxidative stress in diabetes mellitus, multiple studies have suggested that levels of oxidative stress tend to be higher at diagnosis and subsequently decrease over time as glucose control is established.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of diabetes mellitus, chronic hyperglycemia and acute hyperglycemia produce free radicals and thereby increase levels of oxidative stress. 277 Most [278][279][280][281][282][283][284][285] but not all 286 studies report that oxidative stress levels are higher in youth with T1DM compared with healthy control subjects. Consistent with the hypothesis that uncontrolled hyperglycemia is one of the primary mechanisms responsible for oxidative stress in diabetes mellitus, multiple studies have suggested that levels of oxidative stress tend to be higher at diagnosis and subsequently decrease over time as glucose control is established.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Consistent with the hypothesis that uncontrolled hyperglycemia is one of the primary mechanisms responsible for oxidative stress in diabetes mellitus, multiple studies have suggested that levels of oxidative stress tend to be higher at diagnosis and subsequently decrease over time as glucose control is established. [282][283][284][285]287 Evidence suggests that oxidative stress in pediatric T1DM is associated with inflammation, endothelial activation, and other early signs of vascular dysfunction. 98,288,289,291 Although intervention studies are few, 1 study reported that vitamin E supplementation reduced levels of oxidative stress among children with T1DM.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…The HbA1c level is an indicator of the close relation between protein oxidation and glycation in type 2 diabetic patients 8,18 . Kostolanska et al showed that both glycative and oxidative stress were increased in a poor glycemic control diabetic group compared with controls and this contributed to the development of diabetic complications 19 .…”
Section: Hemoglobin Oxidationmentioning
confidence: 99%
“…Meanwhile, soluble forms of RAGE receptors (sRAGE) have also been identified, which may act as decoy receptors, competing with the RAGE for AGE binding, thus limiting the development of vascular diabetic complications [25][26][27]. However, none of the currently published studies that have presented AGEs, sRAGE and other cytokines or growth factors specify threshold values which would point to the presence of microangiopathy in children with T1DM [20][21][22][28][29][30]. Therefore, the aim of this study was to estimate the threshold values for serum concentrations of AGEs, and sRAGE, as well as TNFa, VEGF 165 and IL-12 in predicting the occurrence of microangiopathy in children and adolescents with T1DM.…”
Section: Introductionmentioning
confidence: 99%